Stop, think SCORTCH: rethinking the traditional 'TORCH' screen in an era of re-emerging syphilis. Issue 2 (25th June 2020) - Penner, Justin; Hernstadt, Hayley; Burns, James Edward; Randell, Paul; Lyall, Hermione
Abstract : Background: The epidemiology of congenital infections is ever changing, with a recent resurgence in syphilis infection rates seen in the UK. Identification of congenital infection is often delayed; early recognition and management of congenital infections is important. Testing modalities and investigations are often limited, leading to missed diagnostic opportunities. Methods: The SCORTCH (syphilis, cytomegalovirus (CMV), 'other', rubella, toxoplasmosis, chickenpox, herpes simplex virus (HSV) and blood-borne viruses) acronym increases the awareness of clinicians to the increased risk of congenital syphilis, while considering other infectious aetiologies including: zika, malaria, chagas disease, parvovirus, enterovirus, HIV, hepatitis B and C, and human T-lymphotropic virus 1, in addition to the classic congenital infections recognised in the 'TORCH screen' (toxoplasmosis, 'other', rubella, CMV, HSV). The SCORTCH diagnostic approach describes common signs present in infants with congenital infection, details serological testing for mother and infant and important direct diagnostics of the infant. Direct diagnostic investigations include: radiology, ophthalmology, audiology, microbiological and PCR testing for both the infant and placental tissue, the latter also warrants histopathology. Conclusion: The traditional 'TORCH screen' focuses on serology-specific investigations, often omits important direct diagnostic testing of the infant, and fails to consider emerging and re-emerging congenital infections. In recognition of syphilis as a re-emerging pathogen and the overlapping clinical presentations of various infectious aetiologies, we advocate for a broader outlook using the SCORTCH diagnostic approach.